Thromboembolic Prophylaxis for Total Knee Arthroplasty in Asian Patients: A Randomised Controlled Trial - PL Chin; MS Amin; KY Yang; SJ Yeo; NN Lo (Journal of Orthopaedic Surgery, 2009)
Purpose. To compare the efficacy and safety of different modes of thromboembolic prophylaxis for elective total knee arthroplasty (TKA) in Asian patients. Methods. 440 low-risk patients undergoing TKA were randomised into 4 equal groups: (1) no prophylaxis (control), (2) graduated compression stockings (GCS), (3) intermittent pneumatic compression (IPC), and (4) low-molecular-weight heparin (enoxaparin). Duplex ultrasonography was used as an assessment tool. Results. The deep vein thrombosis point prevalence was highest in the control group (22%), which was significantly higher than in patients receiving IPC (8%, p=0.032) or enoxaparin (6%, p=0.001). One patient each in the control and GCS groups developed a non-fatal pulmonary embolism. Patients on enoxaparin received more blood transfusions and 2 of them had major bleeding complications. Conclusion. IPC is the preferred method of thromboprophylaxis for TKA in Asian patients.